On the affinity of Isocypridinae and Herpetocypridinae, with redescriptions of four species of Ilyodromus Sars, 1894 (Crustacea, Ostracoda) - Shearn, Rylan; Koenders, Annette; Schön, Isa; Halse, Stuart; Martens, Koen (Zootaxa, 2017)
In previous studies, the high degree of similarity of some species of Ilyodromus Sars, 1894 (Herpetocypridinae) to species of another subfamily (Isocypridinae) was noted, calling for a revision of their systematic placement. Here, the systematics of Ilyodromus Sars, 1894 are revised within this context by redescribing four species and comparing these to other genera of Herpetocypridinae and Isocypridinae. Material for the four redescribed species (I. amplicolis De Deckker, 1981, I. dikrus De Deckker, 1981, I. candonites De Deckker, 1981, and I. williamsi (McKenzie, 1966)) was obtained from Museum Victoria and recollected topotypes. It was found that most genera within Isocypridinae share morphological characters that are diagnostic of the subfamily Herpetocypridinae. On these grounds, the transfer of Isocypridinae to the rank of Tribe Isocypridini Rome, 1965 of subfamily Herpetocypridinae Kaufmann, 1900 is proposed here to account for the present understanding of morphological similarity.